Polymorphisms of the human IL-1 receptor antagonist gene and forearm bone mineral density in postmenopausal women - Jivka T Ivanova; Mihail A Boyanov; Andon K Toshev (Indian Journal of Endocrinology and Metabolism, 2012)
Context: Studies on the human interleukin 1 receptor antagonist (IL-1RA) gene polymorphism have provided conflicting data regarding the bone mass and quality. Aim and Design: The objective of this case-control study was to investigate the association between the forearm bone mineral density (BMD) and the IL1RA gene polymorphisms. Materials and Methods: A total of 400 postmenopausal Bulgarian women participated in this study. BMD was measured at the forearm by X-ray absorptiometry on a DTX-100 device (Osteometer Meditech, USA). A PCR product was isolated. The alleles were scored according to their length: A1 - 410 bp - 4 repeats; A2 - 240 bp - 2 repeats; A3 - 500 bp - 5 repeats; A4 - 325 bp - 3 repeats; A5 - 595 bp - 6 repeats. All analyses were evaluated for statistical significance (χ2 -test and T-test). Results: Four alleles were observed - A1, A2, A3, and A4. The A1A1 genotype was more common in cases with low BMD than in controls with normal BMD (95% vs. 90%, χ2 P < 0.01). The A2A2 genotype was equally distributed among cases and controls (both 5%). The other two genotypes (A3A3 and A4A4) as well as A1A3 were present only in controls with normal BMD. The A2A2 genotype was associated with higher BMD and the A1A1 - with lower BMD at both forearm sites. The odds ratio for low BMD in the presence of the A1A1 genotype was 2.11. The etiological factor reflecting the association between the polymorphism and the disease was 0.50. In our study sample the IL1RA genetic polymorphisms were associated with the forearm BMD. Conclusion: This genetic polymorphism may become a useful genetic marker for the study of osteoporosis.